A systems theoretic process analysis (STPA) approach for analyzing the governance structure of fecal sludge management in Japan. (October 2022) - Bugalia, Nikhil; Choudhury, Surjyatapa R; Maemura, Yu; Seetharam, KE
Fecal sludge management (FSM) stakeholders have hitherto been unable to benefit from analytical approaches based on systems thinking principles, as studies utilizing theoretical frameworks to analyze governance structures remain in a nascent stage. One such prominent framework is the Systems Theoretic Process Analysis (STPA), which has no FSM-related applications in the literature. Relying on official documents such as ministerial ordinances, this study conducts a multistage STPA for a well-established and sustainable FSM system, that is, the Johkasou system in Japan. The analysis maps the key stakeholders and their interactions to comprehensively identify potential risks and corresponding novel indicators to help manage risks within the Johkasou system. The features of governance structure thus obtained also highlight the steps necessary to address governance issues for Japan and other countries attempting to establish sustainable FSM. The study extends the STPA literature by providing a substantial validity of STPA's capability for analyzing the FSM governance structure against robust and independent criteria that define the objectives of a "good" governance structure, that is, efficiency, accountability, and legitimacy. The STPA results identify novel leading indicators to guide Japanese policymakers to improve FSM management. The results from STPA also effectively provide valuable insights for other countries by highlighting the various features contributing to an effective governance structure of the Johkasou, such as centralized decision-making in a combination of a hierarchy of goals to establish a clear division of responsibility across various actors. The study also notes potential challenges for field implementation of STPA and discusses directions that future work could explore.